Therapeutic Sequences in the Treatment of High-Risk Prostate Cancer: Paving the Way Towards Multimodal Tailored Approaches - Marvaso, Giulia; Corrao, Giulia; Zaffaroni, Mattia; Pepa, Matteo; Augugliaro, Matteo; Volpe, Stefania; Musi, Gennaro; Luzzago, Stefano; Mistretta, Francesco Alessandro; Verri, Elena; Cossu Rocca, Maria; Ferro, Matteo; et al. (Frontiers in Oncology, 2021)
Various definitions are currently in use to describe high-risk prostate cancer. This variety in definitions is important for patient counseling, since predicted outcomes depend on which classification is applied to identify patient prostate cancer risk category. Historically, strategies for the treatment of localized high-risk prostate cancer comprise local approaches as surgery and radiotherapy and systemic approaches as hormonal therapy. Nevertheless, since high-risk prostate cancer patients remain the group with higher-risk of treatment failure and higher mortality rates, nowadays, novel treatment strategies, comprising hypofractionated-radiotherapy, second-generation antiandrogens and hadrontherapy, are being explored in order to improve their long-term oncological outcomes. This narrative review aims to report the current management of high-risk prostate cancer and to explore the future perspectives in this clinical setting